Characterization of polyethersulfone/Matrimid® 5218 miscible blend mixed matrix membranes for O2/N2 gas separation - Ismail, Ahmad Fauzi; Rahim, R. A.; Rahman, W. A. W. A. (Elsevier B.V., 2008)
This study investigates the gas separation performance of a mixed matrix membranes flat sheet based on polyethersulfone/polyimide (PES/PI) miscible blend incorporated with zeolite particles. Zeolite 4Awas selected and its loadingwere varied between 10 and 50 wt%. Initial attempt of annealing at 150 and 240 ◦C resulted in ideal separation factors far lower than the intrinsic values of the host polymeric membranes. The ideal separation factor was improved by a factor of 5 by increasing the annealing temperature up to 280 ◦C, which is above the glass transition temperature (Tg) of the polymer blend. Only one Tg was observed in DSC analysis, indicating the high miscibility of PES/PI polymer blend and zeolite particles. The ideal separation factors of O2/N2 were higher compared to the value reported for the PES/PI blend membrane and the value increased with increasing zeolite loading. It is concluded that addition of zeolite particles into the matrix of PES/PI polymer blend has significant effect on the membrane structure and properties